Efficacy of endoscopic retrograde cholangiopancreato-graphy in elderly patients - Das, Chittaranjan; Saha, Ashis; Hossain, Faruk; Rahman, Md Mokhlesur; Hasan, Rakibul; Alam, AHM Towhidul (Bangladesh Medical Journal, 2016)
The incidence of biliary tract pathologies increases as the population ages leading to an increase in the demand of therapeutic use of endoscopic retrograde cholangiopancreatography (ERCP). This study was carried out to assess the effectiveness of therapeutic ERCP in elderly patients. It was a prospective observational study. Patients aged 65 years or more referred for therapeutic ERCP from July 2007 to June 2008 were reviewed by a preformed data sheet which included all the relevant details of the procedure. It was collected at the time of ERCP & before discharge. Of 67 patients audited, successful therapeutic ERCP was performed in 91.04% cases. Our study showed that ERCP was effective in the elderly patients. Bangladesh Med J. 2016 Jan; 45 (1): 44-46